Overlapping promoters for two different RNA polymerase holoenzymes control Bradyrhizobium japonicum nifA expression. - Barrios, H (1995)
The Bradyrhizobium japonicum NifA protein, the central regulator for nitrogen fixation gene expression, is encoded in the fixRnifA operon. This operon is activated during free-living anaerobic growth and in the symbiotic root nodule bacteroid state. In addition, it is expressed in aerobic conditions, albeit at a low level. Here, we report that this pattern of expression is due to the presence of two overlapping promoters: fixRp1, which is of the -24/-12 class recognized by the RNA polymerase sigma 54, and fixRp2, which shares homology with the -35 and -10 regions found in other putative B. japonicum housekeeping promoters. Primer extension analyses showed that fixRp1 directed the synthesis of a transcript, P1, that starts 12 nucleotides downstream of the -12 region. In addition to sigma 54, P1 was dependent on NifA and low oxygen tension. Transcripts originating from fixRp2 started at two sites: one coincided with P1, while the most abundant, P2 initiated just two nucleotides further downstream of P1. Expression from fixRp2 was dependent on the upstream -68 promoter region, a region known to bind a putative activator protein, but it was independent of sigma 54 and NifA. This promoter was expressed in aerobic and anaerobic conditions but was not expressed in 30-day-old bacteroids. Mutations in the conserved 12 region for the sigma 54 promoter did not show any transcript, because these mutations also disrupted the overlapping -10 region of the fixRp2 promoter. Conversely, mutations at the -24 region only affected the sigma 54-dependent P1 transcript, having no effect on the expression of P2. In the absence of omega(54), anaerobic expression from the fixRp(2) promoter was enhanced threefold, suggesting that in the wild-type strain, the two RNA polymerase holoenzymes must compete for binding to the same promoter region.